Performance cognitive de futurs professionnels de l’intervention - Larivee, Serge; Normandeau, Sylvie (Canadian Journal of Higher Education, 1984)
Cognitive levels of 48 University students enrolled in humanities were assessed by piagetian tasks. Three specific formal abilities were measured: combinatory, probability, control of variables. For the control of variable tasks, the percentage of students reaching the formal levels did not exceed 50% while that of probabi-lity and combinatory tasks went up to 90%. The results are analyzed according to school training effect and content of tasks.